Improving student understanding of Pancasila values through online learning - Ravita Mega Saputri; Marzuki Marzuki; Suyato Suyato (Fakultas Ilmu Pendidikan, Universitas Negeri Yogyakarta, 2022)
This study aims to analyze the influence of learning media as an effort to increase understanding of Pancasila values through online learning. This study uses quasi-experimental research by providing a pre-test post-test control design. In this study, there were two groups, namely, the experimental group was given to students of Music Arts education and the control group was given to students of German language education. The data collection technique uses a questionnaire that has been made through google forms. The data analysis technique used a normality test, data analysis, standard gain score test, and t-test. The results showed that the normality test using the Kolmogorov-Smirnov statistical technique resulted in the pre-test and post-test results for the control class and the experimental class. The data were normally distributed. Thus, H0 and H1 are accepted, meaning that there are differences in understanding the values of Pancasila between the control class and the experimental class using different learning media. Pembelajaran daring untuk meningkatkan pemahaman pada nilai PancasilaPenelitian ini bertujuan untuk menganalisis pengaruh media pembelajaran sebagai upaya peningkatan pemahaman nilai-nilai Pancasila melalui pembelajaran daring. Penelitian ini menggunakan eksperimen semu (quasi-experimental research) dengan memberikan Pre-test Post-test Control Design. Dalam penelitian ini terdapat dua kelompok yaitu kelompok eksperimen diberikan kepada mahasiswa pendidikan Seni Musik dan kelompok kontrol diberikan kepada mahasiswa pendidikan Bahasa Jerman. Teknik pengumpulan data menggunakan angket yang telah dibuat melalui google formulir. Teknik analisis data menggunakan uji normalitas, analisis data, uji standar gain score, dan uji-t. Hasil penelitian menunjukan uji normalitas dengan teknik statistik Kolmogorov-Smirnov hasil pre-test dan post-test kelas kontrol dan kelas eksperimen data berdistribusi normal. Dengan demikian H0 dan H1 diterima, artinya terdapat perbedaan dalam memahami nilai-nilai Pancasila antara kelas kontrol dan kelas eksperimen dengan menggunakan media pembelajaran yang berbeda